A Study on Business Intelligence and its Impacts in organizations: an overview - KUMAR, P NARESH (IJRDO - Journal of Business Management, 2018)
Business Intelligence disseminates the combinations of Tools, Techniques and approaches towards to perform analytical process which includes collection and integration and analysis of huge un-structured business data to produce value chain for decision making. Business intelligence is a Data-driven systematic process which supports for quality decision making in Modern business environment. Modern business environment each organization Activities always depending on their own ERP Software but These ERP software’s are supporting up to 45-50% for the organization for their operational efficiency in decision making process. Organizations ERP software’s are failed to dig huge volume of data and perform optimal Data Analysis using visualized approaches. This paper mainly concentrating to describe the importance, challenges of Business Intelligence, also describes how to increase performance using business intelligence approach in organizational ERP which supports to reach top place in the competitive business environment .